Peningkatan Keterampilan Menulis Teks Anekdot Melalui Genius Learning Siswa Kelas X Jurusan Bisnis dan Pemasaran SMK Negeri 1 Manado - Yolpi Wukungsenggo (Formosa Journal of Social Sciences (FJSS), 2022)
This study aims to improve the skills of writing anecdotal texts for class X students of the Department of Business and Marketing at SMK Negeri 1 Manado in the 2020/2021 academic year by applying the genius learning strategy. Through genius learning learning strategies. The research model used is Classroom Action Research (CAR). The procedure for implementing the action and implementing the action at the research site is divided into two cycles. The results of the study show the following. First, the use of the genius learning strategy can improve the quality of the anecdote writing learning process. There is an increase in the process in aspects of the learning situation, student focus, and activity, making positive changes so that learning to write anecdotes is more interesting and fun. Second, learning to write anecdotal texts with a genius learning strategy can improve the results of anecdotal writing skills.